2016
DOI: 10.3390/molecules21070963
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Retinol Stabilization of Fatty Amide-β-cyclodextrin Conjugates

Abstract: Amphiphilic cyclodextrin (CD) has been the object of growing scientific attention because of its two recognition sites, the cavity and the apolar heart, formed by self-assembly. In the present study, mono[6-deoxy-6-(octadecanamido)]-β-CD and mono[6-deoxy-6-(octadecenamido)]-β-CD were successfully synthesized by reacting mono-6-amino-6-deoxy-β-CD with N-hydroxysuccinimide esters of corresponding fatty acids in DMF. The structures were analyzed using nuclear magnetic resonance spectroscopy and mass spectrometry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The 24‐h patch test results presented here have shown that there are two cases of (±) doubtful reactions in the 0.1% supramolecular retinol group and eight cases of (±) doubtful reactions in the 0.1% non‐encapsulated retinol group respectively, with significant differences between the two groups. Other studies have shown that retinol can be efficiently encapsulated by cyclodextrins with the benefit of increasing the stability of retinol to light and heat 18,19 . In this study, supramolecular retinol, formed through the hydrophobic/hydrophilic action of cyclodextrin and the inter‐molecular association of supramolecular association agent, improves the stability and reduces irritation in retinol application.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The 24‐h patch test results presented here have shown that there are two cases of (±) doubtful reactions in the 0.1% supramolecular retinol group and eight cases of (±) doubtful reactions in the 0.1% non‐encapsulated retinol group respectively, with significant differences between the two groups. Other studies have shown that retinol can be efficiently encapsulated by cyclodextrins with the benefit of increasing the stability of retinol to light and heat 18,19 . In this study, supramolecular retinol, formed through the hydrophobic/hydrophilic action of cyclodextrin and the inter‐molecular association of supramolecular association agent, improves the stability and reduces irritation in retinol application.…”
Section: Discussionmentioning
confidence: 77%
“…Other studies have shown that retinol can be efficiently encapsulated by cyclodextrins with the benefit of increasing the stability of retinol to light and heat. 18,19 In this study, supramolecular retinol, formed through the hydrophobic/hydrophilic action of cyclodextrin and the inter-molecular association of supramolecular association agent, improves the stability and reduces irritation in retinol application. Taken together, our patch test data indicate that the general safe retinol concentration is less than or equal to 0.1%.…”
Section: Discussionmentioning
confidence: 97%
“…4.II ). Tretinoin which was added in some series of experiments had the published spectrum, 47 with OH signal at 3245 cm −1 , with C 2 H at 2945 cm −1 and 2868 cm −1 , C C at 1623 cm −1 , with CH 2 at 1438 cm −1 and 1363 cm −1 and with H–C C–H at 960 cm −1 . In addition, the pattern for PCL is added in order to allow a mapping of the spun fibers, prepared from PCL, tretinoin and “Ca-polyP-NP”, the complex “PCL/Ca-polyP-NP/Treti” material.…”
Section: Resultsmentioning
confidence: 99%
“…[8,13] Cyclodextrins Solubilization of poorly soluble molecules and protection from chemical degradation. Nanometric diameters (<100 nm) and encapsulation efficiencies ranging from 20-50% [14] Polymeric micelles…”
Section: Solid Lipid Nanoparticlesmentioning
confidence: 99%